2018
DOI: 10.1002/etc.4268
|View full text |Cite|
|
Sign up to set email alerts
|

Microplastics in the aquatic environment: Evidence for or against adverse impacts and major knowledge gaps

Abstract: There is increasing scientific and public concern over the presence of microplastics in the natural environment. We present the results of a systematic review of the literature to assess the weight of evidence for microplastics causing environmental harm. We conclude that microplastics do occur in surface water and sediments. Fragments and fibers predominate, with beads making up only a small proportion of the detected microplastic types. Concentrations detected are orders of magnitude lower than those reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
345
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 546 publications
(358 citation statements)
references
References 166 publications
10
345
1
2
Order By: Relevance
“…However, as recently discussed by Schur et al (2019), caution may be warranted not to overinterpret the potential for translocation based on observations utilizing fluorescence, because results may be characteristic of a study artifact (i.e., lipid accumulation of the leached fraction of hydrophobic fluorescent dye), as opposed to actual particle translocation. Schur et al (2019) attempted to replicate earlier observations, but a general lack of reproducibility of studies that found translocation has been cited as cause for concern (Burns and Boxall, 2018). This is an important cautionary note, in that recent publications (Schur et al 2019; Triebskorn et al 2019) have drawn attention to the inherent challenges that particles face when crossing cellular membranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as recently discussed by Schur et al (2019), caution may be warranted not to overinterpret the potential for translocation based on observations utilizing fluorescence, because results may be characteristic of a study artifact (i.e., lipid accumulation of the leached fraction of hydrophobic fluorescent dye), as opposed to actual particle translocation. Schur et al (2019) attempted to replicate earlier observations, but a general lack of reproducibility of studies that found translocation has been cited as cause for concern (Burns and Boxall, 2018). This is an important cautionary note, in that recent publications (Schur et al 2019; Triebskorn et al 2019) have drawn attention to the inherent challenges that particles face when crossing cellular membranes.…”
Section: Resultsmentioning
confidence: 99%
“…The literature data on ingestion of microplastic particles to include in the present review was initially based on the reference lists reported in several robust reviews recently published for organisms at all levels of biological organization (Schuyler et al 2014; Deudero and Alomar 2015; Lusher et al 2017; Poeta et al 2017; Burns and Boxall 2018; Foley et al 2018; Fossi et al 2018; Hermsen et al 2018; Battisti et al 2019; Botterell et al 2019; Triebskorn et al 2019; Wang et al 2019). The initial list was further complemented by identification of other studies, using a range of methods.…”
Section: Methodsmentioning
confidence: 99%
“…Problem formulation is a critical component, whereby the development of standard test systems should focus on environmental compartments, organisms, and exposure scenarios that are ecologically relevant (Lenz et al 2016;Koelmans et al 2017a;Burns and Boxall 2018). For instance, although there have been several studies assessing effects in various aquatic species, there is currently less understanding of effects for freshwater-, sediment-, and terrestrial-dwelling organisms (Burns and Boxall 2018). But awareness of the environmental fate and exposure potential of microplastic particles for organisms in freshwater systems and sediment is increasing (Corcoran 2015;Blettler et al 2018;Burns and Boxall 2018;Triebskorn et al 2019).…”
Section: Adverse Effects and Dose-response Relationshipsmentioning
confidence: 99%
“…On this global scale, the authors found no immediate risk in marine waters until 2100. Burns and Boxall () published a risk evaluation of microplastics in both freshwaters and marine waters. Their critical review highlighted that organisms are usually exposed in the laboratory to smaller particles and in higher concentrations than those found in the environment.…”
Section: Introductionmentioning
confidence: 99%